The Effectiveness of Cognitive Behavioral Therapy on Resilience and Marital Adjustment among Couples with Marital Conflicts - Faraji , Hana; SamKhaniani, Eshagh; Naghipour , Zeynab; Ghanbari , Maedeh; Ebrahimi Alavige, Elahe (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to determine the effectiveness of cognitive behavioral therapy on resilience and marital adjustment among couples experiencing marital conflicts. Methods and Materials: The present study employed a quasi-experimental method with a pretest–posttest design and a control group. The statistical population consisted of couples with marital conflicts who referred to counseling centers in Tehran during 2025. Using convenience sampling, 28 participants were selected and randomly assigned into two groups, including an experimental group (n = 14) and a control group (n = 14). Data collection instruments included the Connor–Davidson Resilience Scale and the Spanier Dyadic Adjustment Scale. The experimental group participated in eight 2-hour sessions of cognitive behavioral therapy, while the control group received no intervention. Data were analyzed using descriptive statistics and analysis of covariance in SPSS software. Findings: The findings indicated that cognitive behavioral therapy had a significant effect on both resilience and marital adjustment among couples with marital conflicts. The results of covariance analysis demonstrated that the effects of time, group, and the interaction between time and group were statistically significant for resilience and marital adjustment at the p < .001 level. Participants in the experimental group showed significantly higher posttest scores in resilience and marital adjustment compared to the control group, indicating the effectiveness of the intervention in improving psychological resilience and relational functioning. Conclusion: The results of the present study demonstrated that cognitive behavioral therapy is an effective intervention for improving resilience and marital adjustment among couples experiencing marital conflicts. By modifying maladaptive cognitions, enhancing emotional regulation, and improving communication and coping skills, cognitive behavioral therapy can strengthen couples’ psychological adaptability and relational quality. Therefore, CBT-based interventions may be beneficial in counseling and therapeutic settings for reducing marital distress and promoting healthier interpersonal relationships among couples.